THE RELATIONSHIP OF EARLY MARRIAGE AND THE IMPACT OF PREGNANCY IN THE SIPAYUNG HEALTH CENTER AREA - Anggreni, Elsie (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2024)
Early marriage is a marriage carried out by teenagers under the age of 20 who are not yet ready to get married. Pregnancy is the union of spermatozoa and ovum followed by nidation. The aim of this research is to break the relationship between early marriage and the production of 43 pregnancies in the Sipayung Community Health Center Work Area in 2022. The method used is an analytical method with a cross sectional approach. The result was that there were 49% who had early marriage and 51% who did not, 44% who felt the impact of early marriage and 56% who did not feel the impact of early marriage. In conclusion, there is no relationship between early marriage and the impact of pregnancy in the Sipayung Community Health Center Working Area with a P-value of 0.207.